Search for coherent bremsstrahlung from spontaneous fission at 555 meter deep underground laboratory - Deepak Pandit (Elsevier, 2021)
The spectrum of high-energy γ rays accompanying spontaneous fission of 252Cf has been measured in γ-γ coincidence mode to search for the nucleus-nucleus coherent bremsstrahlung. The experiment was performed at the underground laboratory (555 meter depth) which provides a natural attenuation of the cosmic muon flux by a factor of 2 x 104. A total of 2.5 x 1010 fission events were recorded but high-energy γ rays > 25 MeV were not observed at the level as reported in the previous experiments at surface level. The measurement provides a new upper limit at 95% confidence level of 5 x 10−11 photons/(fission x MeV) for γ-ray emission from the nucleus-nucleus coherent bremsstrahlung in 25-180 MeV energy region, which is two orders of magnitude lower than the previous value. The result has been compared with the existing theoretical models. The fully quantum approach and potential barrier included Coulomb acceleration calculation predict two orders of magnitude and one order of magnitude higher emission probability, respectively, in 25-60 MeV energy range compared to the new upper limit indicating towards the modification of the theories.